USING ELEMENTS OF MUSIC THERAPY IN EDUCATIONAL AND REHABILITATION WORK WITH DISABILITIES - Ольга Юрьевна Синевич; Татьяна Юрьевна Четверикова (The Publishing House Medicine and Enlightenment, 2020)
The article displays the specific of music therapy's elements using in educational and rehabilitation work with children with developmental disorders. Examples of exercises and activities recommended for use in the educational process and in extracurricular activities, including correctional classes, to provide specialized assistance to the child are presented. The following recommendations are described for the organization of listening to music, singing, performing musical and rhythmic movements, and playing musical instruments. The article contains information about classical music and natural sounds that help to normalize the emotional conditions of children with disabilities and satisfy their special needs.